2020
DOI: 10.1111/evj.13292
|View full text |Cite
|
Sign up to set email alerts
|

Clinically and temporally specific diagnostic thresholds for plasma ACTH in the horse

Abstract: Background Pituitary pars intermedia dysfunction (PPID) is commonly investigated using plasma ACTH concentrations but problems exist with currently available diagnostic thresholds. Objectives To derive temporally specific diagnostic thresholds for equine plasma ACTH concentration to be used alongside clinical judgement in each individual week of the year and appropriate for the degree of clinical suspicion in any given case. Furthermore, to apply these thresholds to compare the prevalence of high and low ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 28 publications
2
40
2
Order By: Relevance
“…Basal ACTH has been the cornerstone of PPID diagnosis, 5,6 and further research refining the interpretation of basal ACTH concentrations was presented. A study based on a very large cohort of samples presented weekly diagnostic thresholds throughout the year test 7 . Importantly, this study showed a grey zone or a low (95% sensitivity) and high (95% specificity) diagnostic threshold for guiding clinical diagnosis depending on the pretest likelihood of PPID and whether or not the clinician is attempting to confirm or exclude PPID 7 .…”
Section: What Consensus Was Reached Where Is It Lacking and Where Armentioning
confidence: 86%
See 1 more Smart Citation
“…Basal ACTH has been the cornerstone of PPID diagnosis, 5,6 and further research refining the interpretation of basal ACTH concentrations was presented. A study based on a very large cohort of samples presented weekly diagnostic thresholds throughout the year test 7 . Importantly, this study showed a grey zone or a low (95% sensitivity) and high (95% specificity) diagnostic threshold for guiding clinical diagnosis depending on the pretest likelihood of PPID and whether or not the clinician is attempting to confirm or exclude PPID 7 .…”
Section: What Consensus Was Reached Where Is It Lacking and Where Armentioning
confidence: 86%
“…A study based on a very large cohort of samples presented weekly diagnostic thresholds throughout the year test 7 . Importantly, this study showed a grey zone or a low (95% sensitivity) and high (95% specificity) diagnostic threshold for guiding clinical diagnosis depending on the pretest likelihood of PPID and whether or not the clinician is attempting to confirm or exclude PPID 7 . Work on development of a clinical sign score to help determine if endocrine testing is warranted was presented which was considered valuable in improving pretest probabilities.…”
Section: What Consensus Was Reached Where Is It Lacking and Where Armentioning
confidence: 99%
“…7 In our study, a single ACTH concentration was used to classify animals as having or not having increased autumnal ACTH concentrations using a previously established seasonal cutoff point from a study that used the same methodology. 30 While this approach is commonly used in daily equine practice, 31 use of a dynamic test to classify animals might have provided a more standardized approach. 39 It is also possible that the study was underpowered to detect subtle differences in l-lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…30 As second seasonal threshold of ≥76 pg/mL, again established using the same methodology, was also investigated. 31 Animals <1 year of age were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation